ANALYSIS OF FALL RISK IN THE ELDERLY BASED ON CLINICAL AND COGNITIVE ASSESSMENTS AT PANTI WERDHA X, CIBUBUR, EAST JAKARTA - Hastuty, Dewi; Aswar, Andini; Prasetyo, Deril Falah Naufal; Widianto , Muhammad Rafi (Media Inovasi Pendidikan dan Publikasi, 2025)
Background: Older adults are at high risk of falls due to age-related decline in physical, sensory, and cognitive functions. Falls significantly impair quality of life and increase morbidity among nursing home residents. Objective: This study aimed to evaluate the risk factors for falls in the elderly based on clinical and cognitive assessments using a multidimensional approach. Methods: A descriptive observational study with a qualitative approach was conducted on two elderly residents of Panti Werdha X, Cibubur, East Jakarta. Total sampling was applied. Assessments included in-depth interviews, physical examination, and the use of MMSE, Clock Drawing Test (CDT), and Ontario Modified Stratify–Sydney Score. Results: The first subject (Oma T, 78 years) had a low MMSE score (21) and a low fall risk score (OMS: 1), but demonstrated a strong psychological fear of falling. The second subject (Opa D, 77 years) exhibited signs of Parkinsonism, vascular complications, and a history of recurrent falls, with a high OMS score (19). CDT indicated impaired executive function. Conclusion: Fall risk in the elderly is influenced by a combination of intrinsic factors, mild to moderate cognitive impairment, and psychological components such as fear of falling. Multidisciplinary preventive interventions—including routine evaluations, environmental modifications, education, and physical exercises—are essential to reduce fall risk and enhance the quality of life in institutionalized elderly populations.